Fluorination as tool to improve bioanalytical sensitivity and COX-2-selective antitumor activity of cobalt alkyne complexes. Issue 42 (16th October 2019) - Baecker, Daniel; Obermoser, Victoria; Kirchner, Elisabeth Anna; Hupfauf, Andrea; Kircher, Brigitte; Gust, Ronald
Abstract : Fluorination of the lead Co-ASS yielded antitumor active cobalt alkyne complexes that exhibited both improved COX-2 selectivity and better bioanalytical sensitivity. Abstract : The cobalt alkyne complex [(prop-2-ynyl)-2-acetoxybenzoate]dicobalthexacarbonyl (Co-ASS) is an auspicious lead, which exhibits its anticancer activity mainly by inhibition of both cyclooxygenases (COX-1 and COX-2). Since COX-2 participates in carcinogenesis, a selective inhibition of that isoenzyme is aimed. To study if fluorination increases the COX-2/COX-1 inhibition ratio of the lead, substitution was respectively performed in the positions 3, 4, 5, and 6 of the aromatic moiety. The complexes 3/4/5F-Co-ASS and to a much lower extent also 6F-Co-ASS showed cytotoxic, antimetabolic, and apoptotic effects in COX-1/2-positive HT-29 and MDA-MB-231 cells and remarkably less activity in the COX-1/2-negative MCF-7 cell line. The metabolic activity in MCF-7 cells was even unaffected up to a concentration of 40 μM. With exception of 6F-Co-ASS, the complexes strongly reduced the PGE2 synthesis in HT-29 cells and all complexes inhibited COX-2 more effectively than COX-1 in an assay at isolated enzymes. These findings point to an interference in the COX cascade as part of the mode of antitumor action. The limited cellular effects of 6F-Co-ASS are related to its poor uptake as determined by HR CS AAS/MAS. Moreover, the cellular uptake studies confirm fluorination as beneficial tool for bioanalytical labeling. The higher quantification of fluorine by HR CS MAS makes this method about 5-fold more sensitive than HR CS AAS measuring cobalt. As a further positive result, 3/4/5/6-Co-ASS demonstrated high selectivity to tumor cells due to lack of antimetabolic activity against the non-tumorigenic bone marrow stromal cell line HS-5.